Protocols for estimating multiple functions with quantum sensor networks: Geometry and performance - Jacob Bringewatt; Igor Boettcher; Pradeep Niroula; Przemyslaw Bienias; Alexey V. Gorshkov (Physical Review Research, 2021)
We consider the problem of estimating multiple analytic functions of a set of local parameters via qubit sensors in a quantum sensor network. To address this problem, we highlight a generalization of the sensor symmetric performance bounds of Rubio et al., [J. Phys. A 53, 344001 (2020)]1751-811310.1088/1751-8121/ab9d46 and develop an optimized sequential protocol for measuring such functions. We compare the performance of both approaches to one another and to local protocols that do not utilize quantum entanglement, emphasizing the geometric significance of the coefficient vectors of the measured functions in determining the best choice of measurement protocol. We show that, in many cases, especially for a large number of sensors, the optimized sequential protocol results in more accurate measurements than the other strategies. In addition, in contrast to the sensor symmetric approach, the sequential protocol is known to always be explicitly implementable. The sequential protocol is very general and has a wide range of metrological applications.